Pattern of cerebral hyperperfusion in Alzheimer’s disease and amnestic mild cognitive impairment using voxel-based analysis of 3D arterial spin-labeling imaging: initial experience - Ding, Bei (Dove Medical Press, 2014)
PURPOSE: A three-dimensional (3D) continuous pulse arterial spin labeling (ASL) technique was used to investigate cerebral blood flow (CBF) changes in patients with Alzheimer’s disease (AD), amnestic mild cognitive impairment (aMCI), and age- and sex-matched healthy controls. MATERIALS AND METHODS: Three groups were recruited for comparison, 24 AD patients, 17 MCI patients, and 21 age- and sex-matched control subjects. Three-dimensional ASL scans covering the entire brain were acquired with a 3.0 T magnetic resonance scanner. Spatial processing was performed with statistical parametric mapping 8. A second-level one-way analysis of variance analysis (threshold at P<0.05) was performed on the preprocessed ASL data. An average whole-brain CBF for each subject was also included as group-level covariates for the perfusion data, to control for individual CBF variations. RESULTS: Significantly increased CBF was detected in bilateral frontal lobes and right temporal subgyral regions in aMCI compared with controls. When comparing AD with aMCI, the major hyperperfusion regions were the right limbic lobe and basal ganglia regions, including the putamen, caudate, lentiform nucleus, and thalamus, and hypoperfusion was found in the left medial frontal lobe, parietal cortex, the right middle temporo-occipital lobe, and particularly, the left anterior cingulate gyrus. We also found decreased CBF in the bilateral temporo-parieto-occipital cortices and left limbic lobe in AD patients, relative to the control group. aMCI subjects showed decreased blood flow in the left occipital lobe, bilateral inferior temporal cortex, and right middle temporal cortex. CONCLUSION: Our results indicated that ASL provided useful perfusion information in AD disease and may be used as an appealing alternative for further pathologic and neuropsychological studies, especially of compensatory mechanisms for cerebral hypoperfusion.